Efficacy and safety of mesenchymal stem cell therapy in acute on chronic liver failure: a systematic review and meta-analysis of randomized controlled clinical trials - Lu, Wenming; Yan, Longxiang; Peng, Lulu; Wang, Xuesong; Tang, Xingkun; Du, Jing; Lin, Jing; Zou, Zhengwei; Li, Lincai; Ye, Junsong; Zhou, Lin (Stem cell research & therapy, 2025)
Acute-on-chronic liver failure has become a serious global health burden, which is characterized by an acute deterioration of liver function, rapidly evolving organ failure, and high short-term mortality in patients with chronic liver disease. The pathogenesis includes extensive hepatic necrosis, which is related to intense systemic inflammation and subsequently causes the inflammatory cytokine storm, resulting in portal hypertension, organ dysfunction, and organ failure. Mesenchymal stem cells can function as seed cells to remodel and repair damaged liver tissues, thus showing potential therapeutic alternatives for patients with chronic liver disease. However, standard treatment protocols for mesenchymal stem cells in acute-on-chronic liver failure patients have not been established. We conducted a detailed search from PubMed/Medline, Web of Science, EMBASE, and Cochrane Library to find randomized controlled trials published before October 23, 2021. We formulated criteria for the literature screening according to the PICOS principle (Population, Intervention, Comparison, Outcome, Study design). Subsequently, the bias risk assessment tool was used to assess the quality of all enrolled studies. Finally, outcome measurements including the model of end-stage liver disease score, albumin, total bilirubin, coagulation function, and aminotransferase were extracted for statistical analysis. A total of 7 clinical trials were included. The results of enrolled studies indicated that patients with acute-on-chronic liver failure who received mesenchymal stem cells inoculation showed a decreased MELD score in 4 weeks and 24 weeks, compared with counterparts who received conventional treatment. Reciprocally, mesenchymal stem cells inoculation improved the ALB levels in 4 weeks and 24 weeks. For secondary indicators, mesenchymal stem cells treatment significantly reduced INR levels and ALT levels, compared with the control group. Our results showed no significant differences in the incidence of adverse reactions or serious adverse events monitored in patients after mesenchymal stem cells inoculation. This meta-analysis indicated that mesenchymal stem cell infusion is effective and safe in the treatment of patients with acute-on-chronic liver failure. Without increasing the incidence of adverse events or serious adverse events, MSC treatment improved liver function including a decrease in MELD score and an increase in ALB levels in patients with acute-on-chronic liver failure. However, large-cohort randomized controlled trials with longer follow-up periods are required to further confirm our conclusions.